The impact of commercial banks development on economic growth in Namibia - Paavo, Elia (Research of GSB, 2018)
This study sets out to investigate the impact of commercial banks development on economic growth in Namibia. Using quarterly data on GDP as well as various commercial banks development indicators, covering the period March 2005 to December 2016, the study employed the Auto-Regression Distributive Lag (ARDL) methodology in determining existence of the short-run and long-run relationships. Furthermore, the study employed the Granger causality test in determining the causal relationship between banking sector development and economic growth. From the ARDL results, the study concluded that there is existence of a positive short-run relationship between banking sector development and GDP growth, channelled through net interest income and funding liabilities of banks. The causality test indicated a bi-directional causality between economic growth and the banking sector development, entailing that development of the banking sector would enhance GDP growth and vice versa. The study thus concluded that, commercial banks development has an impact on economic growth in Namibia and recommends for reforms in the banking industry to ensure increased lending in order to support the economy.